Involvement of Physical Parameters in Medium Improvement for Tannase Production by Aspergillus niger FETL FT3 in Submerged Fermentation. (28th July 2011) - Darah, I.; Sumathi, G.; Jain, K.; Hong, Lim Sheh
Abstract : Aspergillus niger FETL FT3, a local extracellular tannase producer strain that was isolated from one of dumping sites of tannin-rich barks of Rhizophora apiculata in Perak, Malaysia. This fungus was cultivated in 250 mL Erlenmeyer flask under submerged fermentation system. Various physical parameters were studied in order to maximize the tannase production. Maximal yield of tannase production, that is, 2.81 U per mL was obtained on the fourth day of cultivation when the submerged fermentation was carried out using liquid Czapek-Dox medium containing (percent; weight per volume) 0.25% NaNO3, 0.1% KH2 PO4, 0.05% MgSO4 ·7H2 O, 0.05% KCl, and 1.0% tannic acid. The physical parameters used initial medium pH of 6.0, incubation temperature of30 ∘ C, agitation speed of 200 rpm and inoculums size of6 × 10 6 spores/ ml. This research has showed that physical parameters were influenced the tannase production by the fungus with 156.4 percent increment.